2022
DOI: 10.12688/f1000research.128868.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a self-sufficient photovoltaic system for a remote, off-grid community

Abstract: Background A photovoltaic (PV) system, especially the stand-alone type, along with a battery storage system, plays a significant role in providing the needed electrical energy to remote, off-grid communities. Methods  In this study, a stand-alone PV solar cell was enhanced to better understand the system operation. Modeling and simulation were performed using MATLAB software. Results  This work has shown that the I-V  (current-voltage) and P-V (power-voltage) characteristics of the modelled system have a profo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The optimization of PV systems, including battery storage and efficient design, is vital for ensuring reliable energy supply in off-grid locations. By utilizing renewable energy sources like solar power, these systems not only enhance energy access but also contribute to reducing carbon emissions, making them a cost-effective and environmentally friendly solution for remote electrification [9].…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of PV systems, including battery storage and efficient design, is vital for ensuring reliable energy supply in off-grid locations. By utilizing renewable energy sources like solar power, these systems not only enhance energy access but also contribute to reducing carbon emissions, making them a cost-effective and environmentally friendly solution for remote electrification [9].…”
Section: Introductionmentioning
confidence: 99%
“…PV energy is more affordable than any other sustainable energy source, and research has shown that it is incredibly profitable in rural regions. 11 , 12 At every stage of the global solar PV supply chain, China is currently by far the largest supplier; with a manufacturing capacity for PV modules of around 340 GW/year, it has more than twice the installed PV modules worldwide, with a manufacturing capacity utilization rate for solar components of between 40 and 50% in 2021. China directly supplies all markets, except North America, where import taxes on Chinese solar PV components have been imposed.…”
Section: Introductionmentioning
confidence: 99%
“…27 Various case studies on the PV performance are accomplished by researchers by considering certain locations, 28,29 based on techno-economic assessment, 30,31 feasibility studies, 32,33 comparative studies, 34 optimizing the performance, 35 solar insolation studies and estimations [36][37][38] and several other factors. [39][40][41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%